Assessing structural integrity of non-homogeneous systems by means of Acoustic Emissions and Non-Extensive Statistical Mechanics (Fracture and Structural Integrity, 2024)
Taking advantage of the interevent time intervals, namely the time intervals between two successive acoustic events recorded during mechanical loading of structural elements, it is attempted to detect indices warning about upcoming failure. The innovative aspect of the study is that the analysis is implemented in the frame of Non-Extensive Statistical Mechanics, a discipline founded on a class of entropies violating the additivity principle, which is the cornerstone of the Boltzmann-Gibbs Statistical Mechanics. The specimens used for the experiments were marble blocks simulating either fragmented and restored epistyles or mutually interconnected intact epistyles of the Parthenon Temple on the Acropolis of Athens. The specimens consisted of three materials (marble, metallic connectors and cementitious pastes) exhibiting, thus, a strongly non-homogeneous nature. The entropic index, i.e., the parameter quantifying the degree of non-additivity, was used for the analysis of the experimental data. The results were considered in juxtaposition to the respective ones from experimental protocols with specimens of macroscopically homogeneous nature. It was concluded that the temporal evolution of the entropic index provides very good insight into the level of damage accumulated in the loaded structure, independently of whether the structure is homogeneous or not, providing an interesting pre-failure indicator.
Keywords: Structural Integrity; Structural Health Monitoring; Pre-failure indices; Interevent times; Non-Extensive Statistical Mechanics; Non Additive Entropies